Java 13 Revealed : for early adoption and migration - Sharan, Kishori; SpringerLink (Online service); O'Reilly (Firm); Serials Solutions (New York : Apress, 2019)
Explore the new Java programming language features and APIs introduced in Java 10 through Java 13. Java 13 Revealed is for experienced Java programmers looking to migrate to Java 13. Author Kishori Sharan begins by covering how to use local variable type inference to improve readability of your code and time-based release versioning of the Java platform to understand the Java release strategy. This book provides extensive coverage of the new HTTP Client APIs, which were introduced in Java 9 as a preview and was made a standard feature in Java 11. New Java features such as launching a single-file source code program and new switch syntax are discussed in detail. You will: Use local variable type inference to declare local variables using the var restricted type name introduced in Java 10 Take advantage of application class data sharing among JVMs for faster application startup Create HTTP requests, responses, and web sockets with the new HTTP Client APIs Run a single-file Java source code program using the java command without compiling it Apply the new switch statement and expressions to write compact and less error-prone code Work with text blocks in Java code About new APIs, deprecated APIs, and deprecated tools.
1: Local Variable Type Inference -- 2: Java Versioning Scheme -- 3: The HTTP Client API -- 4: Launching Single File Source Code Programs -- 5: Enhanced Switch -- 6: Text Blocks -- 7: Class Data Sharing -- 8: Tools and APIs Changes.
Mode of access: World Wide Web.
Keywords: Local variable type inference; Enhanced switch; tools and APIs changes; Electronic books